Contemporary Russian nationalisms: the state, nationalist movements, and the shared space in between. Issue 2 (20th November 2018) - Laine, Veera
Abstract : For several years, various nationalist groups and the Russian state have been competing over nationalism as a political concept and for popular support to nationalist claims. This paper analyzes the relationship between the state and anti-government, ethnocentric nationalistic groups that gather annually in an event called "the Russian March." Emphasis is on the change in that relationship that happened in 2014, when the state added efforts to channel and mobilize the nationalists to its previous repressive and controlling measures. The article conceptualizes the competition over the nationalist argument in contemporary Russia as a case of dissentful and consentful contention in hybrid regimes, and shows how the dissentful nationalists have been forced to make way for the more consentful ones. Until recently, the room for maneuver for the radical nationalists was relatively wide. The events in Ukraine, however, divided the nationalists, and since 2014 radical nationalists have faced increased state repression. At the same time, pro-government nationalist actors have strengthened, and new players have appeared in the field. These developments tell us not only about the Kremlin's diminished tolerance for dissentful contention, but also about the importance of the nationalist argument in Russian politics today.